1995
DOI: 10.1002/jms.1190300221
|View full text |Cite
|
Sign up to set email alerts
|

Thin‐layer chromatography/laser desorption of peptides followed by multiphoton ionization time‐of‐flight mass spectrometry

Abstract: The location of the separated compounds of GlnTrp/GlyTyr and pentagastrinlgramicidin D peptide model mixtures on silica gel and cellulose thin-layer chromatography plates has been examined by laser desorption multiphoton ionization time-of-flight mass spectrometry. The multiphoton ionization mass spectra of neutrals desorbed by sequential scanning of the thin-layer chromatography plates versus the infrared laser spot allowed imaging of the distribution profile of the compounds. The method appeared to be promis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…21 Because of its sensitivity, selectivity, and potential to be quantitative, postionization has been applied to many different areas of research. A few examples of surface analysis of molecular species using postionization include peptides desorbed from thinlayer chromatography plates, 22 polycyclic aromatic hydrocarbons from meteoritic acid residues, 23 and imaging of patterned biomolecules and polymers deposited on various surfaces. [24][25][26] It was previously suggested that postionization mass spectrometry could be used to characterize molecular biosensors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…21 Because of its sensitivity, selectivity, and potential to be quantitative, postionization has been applied to many different areas of research. A few examples of surface analysis of molecular species using postionization include peptides desorbed from thinlayer chromatography plates, 22 polycyclic aromatic hydrocarbons from meteoritic acid residues, 23 and imaging of patterned biomolecules and polymers deposited on various surfaces. [24][25][26] It was previously suggested that postionization mass spectrometry could be used to characterize molecular biosensors.…”
mentioning
confidence: 99%
“…Because of its sensitivity, selectivity, and potential to be quantitative, postionization has been applied to many different areas of research. A few examples of surface analysis of molecular species using postionization include peptides desorbed from thin-layer chromatography plates, polycyclic aromatic hydrocarbons from meteoritic acid residues, and imaging of patterned biomolecules and polymers deposited on various surfaces. It was previously suggested that postionization mass spectrometry could be used to characterize molecular biosensors . However, mass spectrometric studies of host−guest chemistry at surfaces have been mainly confined to matrix-assisted laser desorption and fast-atom bombardment. Both of these methods often require extensive sample treatments that may not be appropriate in certain applications.…”
mentioning
confidence: 99%
“…However, LD produces significant molecular fragmentation and has poor reproducibility. Fragmentation can be reduced by using IR laser desorption followed by multiphoton ionization (MUPI) [18][19][20][21], but the technique requires sophisticated instrumentation and is not applicable to a broad range of compounds.…”
Section: Introductionmentioning
confidence: 99%
“…However, conventional LD‐TLC/MS based on a UV laser suffers from extensive fragmentation due to the high laser power, which is required for the ionization of the analytes. Consequently, infrared (IR) laser desorption from TLC plates, followed by a post‐ionization step, was developed and applied by several groups 7–10…”
mentioning
confidence: 99%